Prevalence of Giardia spp in rodents (Rattus spp) of a zoo in Metropolitan Lima - Casana P., Cynthia (2019)
The aim of this study was to determine the prevalence of Giardia spp in rodents (Rattus rattus and Rattus norvegicus) captured in a zoo in Metropolitan Lima, as well as the possible association between the presence of the parasite with the species, sex and age of the rats. A total of 127 rodents (Rattus spp) were captured between February 2013 and August 2016 by using live capture traps "Tomahawk". The handling of the rodents and the collection of the samples complied with biosafety standards and processing standards in accordance with the protocols of the Center for Infectious Diseases and Prevention of Atlanta (CDC). Samples of the small intestine and posterior digestive tract (caecum, colon and rectum) were collected and preserved with 10% formaldehyde. The modified Ritchie technique was used, considering as a positive sample the presence of some parasitic form of Giardia spp (trophozoite or cyst). The prevalence of Giardia spp in rodents was 5.5 ± 0.04% (7/127), being 2.1% in R. rattus (1/48) and 7.6% in R. norvergicus (6/79). No significant association was found between the frequency of Giardia spp and the species, sex and age. A low prevalence of Giardia spp is reported in rodents captured at the zoo; however, there could be a potential risk of parasitic infection for those attending, mainly children and the elderly, as well as animals and workers of the institution.